THE INFLUENCE OF ORGANIZATIONAL CULTURE ON THE EMPLOYEE PERFORMANCE MEDIATED BY JOB SATISFACTION AND ORGANIZATIONAL COMMITMENT - Wua, Injilia Wulan Gratia; Noermijati, Noermijati; Yuniarinto, Agung (Universitas Brawijaya, Indonesia, 2022)
The digital era is now making competition between companies increasingly competitive. Companies need to pay attention to and improve the performance of existing human resources to be able to compete. This research aims to test and analyze the direct and indirect influence between organizational culture and employee performance with the mediator variable, job satisfaction, and organizational commitment. The quantitative analysis was used in this research, and there were 112 employees of Bank SulutGo of Manado Main Branch Office as the samples were collected through questionnaires. Furthermore, the analytical instrument to analyze these data was Smart PLS 3.0. The results showed that organizational culture has a direct and significant influence on employee performance. Organizational culture has a direct and significant influence on job satisfaction. Organizational culture has a direct and significant influence on organizational commitment. Organizational commitment has a direct and significant influence on employees' performance. Job satisfaction has a direct and significant influence on employees' performance. Job satisfaction influences organizational commitment. However, organizational commitment is the one that has the biggest influence on improving employee performance. Moreover, job satisfaction and organizational commitment can mediate the relationship between organizational culture and employee performance with partial mediation. The results of this study will help companies to improve employee performance, so that companies can compete in digital era.